2016
DOI: 10.1136/vr.103529
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of commercial type 1 and type 2 PRRSV vaccines against heterologous dual challenge

Abstract: This study was to compare the effect of vaccination of pigs with either type 1 or type 2 porcine reproductive and respiratory syndrome virus (PRRSV) against heterologous dual challenge of both genotypes. Pigs were administered type 1 (UNISTRAIN PRRS) or type 2 (Fostera PRRS) PRRSV vaccine at 28 days of age and inoculated intranasally with both genotypes at 63 days of age. Vaccination of pigs with type 1 PRRSV was able to reduce the levels of type 1 but not type 2 PRRSV viraemia, whereas vaccination of pigs wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
15
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 29 publications
4
15
1
Order By: Relevance
“…Our results are in agreement with those of a previous single challenge study that demonstrated partial cross-protection by PRRSV MLV 15, 16,22,[41][42][43][44] . On the other hand, our cross-protection results are in contrast with those of another previous dual-challenge study in which vaccination with PRRSV-1 MLV reduced only PRRSV-1 viremia and not PRRSV-2 viremia 45 . Pigs vaccinated with PRRSV-1 MLV showed no reductions in PRRSV-2 antigens in lung tissues.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results are in agreement with those of a previous single challenge study that demonstrated partial cross-protection by PRRSV MLV 15, 16,22,[41][42][43][44] . On the other hand, our cross-protection results are in contrast with those of another previous dual-challenge study in which vaccination with PRRSV-1 MLV reduced only PRRSV-1 viremia and not PRRSV-2 viremia 45 . Pigs vaccinated with PRRSV-1 MLV showed no reductions in PRRSV-2 antigens in lung tissues.…”
Section: Discussioncontrasting
confidence: 99%
“…Some studies have found similar incomplete effect of vaccination following challenge of PRRSV-1 vaccinated pigs with heterologous PRRSV-1 strains [17,26], while others have found significant reduction in viremia following PRRSV-1 vaccination in a quasi-natural experimental model [27] and clinical protection in the field despite the field strain was only 85% identical to the vaccine strain in ORF 5 [19]. In the present study, vaccination against PRRSV-1 did not protect against challenge with Type 2 virus which are in accordance with the majority of previous studies [26,[28][29][30]. The challenge in the present study was performed approximately two months after vaccination which is later than in most vaccine trials.…”
Section: Discussionsupporting
confidence: 92%
“…However, it must be noted that, because of interference of type 2 PRRSV on type 1 PRRSV replication during coinfection, type 1 PRRSV-specific viraemia levels and type 1 PRRSV-positive lung cells were not significantly different among type 1 vaccinated/dual challenge, type 2 vaccinated/dual challenge and unvaccinated/dual challenge groups. Therefore, based solely on the data obtained in this single study (Choi and others 2016), it cannot be concluded that vaccination of pigs with a type 1 vaccine was able to reduce the levels of type 1 PRRSV viraemia after dual challenge; neither can it be concluded that vaccination of pigs with a type 2 vaccine was able to reduce the levels of type 1 PRRSV viraemia after dual challenge. However, previous studies (Kim and others 2015, Park and others 2015a, 2015b, 2015c) support the conclusions that the type 1 vaccine, UNISTRAIN PRRS or Porcilis PRRS, or the type 2 Fostera PRRS vaccine, was able to reduce the type 1 PRRSV viraemia level in single-vaccination single-challenge models.…”
Section: Vaccination Strategies Against Single or Dual Infections Witmentioning
confidence: 77%
“…In a paper summarised on p 291 of this issue of Veterinary Record , Choi and others (2016), from a research group lead by Chanhee Chae, compare commercial type 1 and type 2 PRRSV vaccines against heterologous dual challenge, adding to papers already published by this research group investigating the pathogenicity of type 1 and type 2 PRRSV coinfection as well as vaccination strategies.…”
mentioning
confidence: 99%